2015
DOI: 10.4314/mmj.v27i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to defaulting scheduled therapy sessions by caregivers of children with congenital disabilities

Abstract: Background Defaulting scheduled rehabilitation therapy may result in increased adverse outcomes such as permanent disability and increased healthcare costs. Concomitantly, there is evidence to suggest that early and continued rehabilitation of children with congenital disabilities can improve outcomes significantly. This study was conducted to determine factors contributing to caregivers' defaulting scheduled rehabilitation therapy sessions. Methods A descriptive cross sectional study was carried out at Chitun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 14 publications
(16 reference statements)
0
26
0
Order By: Relevance
“…Although there were 29 countries in Africa that allocated less than $50 per person to healthcare, papers included in this study were from only nine Sub-Saharan countries. Of the 15 articles discussed in this review, four papers reported on Ethiopia [11][12][13], two on Zimbabwe [14,15], two on Malawi [16,17], two on Cote d'Ivoire [18,19], one on Rwanda and Uganda [20], one on Uganda [21], one on Kenya [22], one on Zambia [23] and one on Nigeria [24] (Table 1 in Appendix).…”
Section: Study Screening Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although there were 29 countries in Africa that allocated less than $50 per person to healthcare, papers included in this study were from only nine Sub-Saharan countries. Of the 15 articles discussed in this review, four papers reported on Ethiopia [11][12][13], two on Zimbabwe [14,15], two on Malawi [16,17], two on Cote d'Ivoire [18,19], one on Rwanda and Uganda [20], one on Uganda [21], one on Kenya [22], one on Zambia [23] and one on Nigeria [24] (Table 1 in Appendix).…”
Section: Study Screening Resultsmentioning
confidence: 99%
“…Stigma, including experienced stigma and fear of stigmatization, was a reported barrier in five papers. High levels of stigma were reported by many families of children with disabilities, preventing them from allowing their children to access health care and proper medical treatment [11,12,15,23] . Caregivers in Ethiopia, Zimbabwe, and Zambia expressed concerns about being treated poorly by others and how this caused them to decide to hide their child's condition instead of seeking treatment [11,12,15,23].…”
Section: Theme 1: Attitudes Beliefs and Awareness Of Disability Stigmamentioning
confidence: 99%
See 3 more Smart Citations